Lausanne Declaration on Doping in Sport
Lausanne Declaration on Doping in Sport Adopted by the World Conference on Doping in Sport 4 February 1999, Lausanne, Switzerland Considering that doping practices contravene sport and medical ethics, and that they constitute violations of the rules established by the Olympic Movement, and concerned by the threat that doping poses to the health of athletes and youth in general; Recognizing that the fight against doping in sport is the concern of all: the Olympic Movement and other sports organizations, governments, inter-governmental and non-governmental organizations, sportsmen and sportswomen throughout the world, and their entourage; The World Conference on Doping in Sport, with the participation of representatives of governments, of inter-governmental and non-governmental organizations, of the International Olympic Committee (IOC), the International sports Federations (IFs), the National Olympic Committees (NOCs), and of the athletes, declares: 1. Education, prevention and athletes' rights The Olympic oath shall be extended to coaches and other officials, and shall include the respect of integrity, ethics and fair play in sport. Educational and preventive campaigns will be intensified, focusing principally on youth, and athletes and their entourage. Complete transparency shall be assured in all activities to fight doping, except for preserving the confidentiality necessary to protect the fundamental rights of athletes. Partnership with the media shall be sought in anti-doping campaigns. 2. Olympic Movement Anti-Doping Code The Olympic Movement Anti-Doping Code is accepted as the basis for the fight against doping, which is defined as the use of an artifice, whether substance or method, potentially dangerous to athletes' health and/or capable of enhancing their performances, or the presence in the athlete's body of a substance, or the ascertainment of the use of a method on the list annexed to the Olympic Movement Anti-Doping Code. The Olympic Movement Anti-Doping Code applies to all athletes, coaches, instructors, officials, and to all medical and paramedical staff working with athletes or treating athletes participating in or training for sports competitions organized within the framework of the Olympic Movement. 3. Sanctions The sanctions which apply to doping violations will be imposed in the framework of controls both during and out of competition. In accordance with the wishes of the athletes, the NOCs and a large majority of the IFs, the minimum required sanction for major doping substances or prohibited methods shall be a suspension of the athlete from all competition for a period of two years, for a first offence. However, based on specific, exceptional circumstances to be evaluated in the first instance by the competent IF bodies, there may be a provision for a possible modification of the two-year sanction. Additional sanctions or measures may be applied. More severe sanctions shall apply to coaches and officials guilty of violations of the Olympic Movement Anti-Doping Code. 4. International Anti-Doping Agency An independent International Anti-Doping Agency shall be established so as to be fully operational for the Games of the XXVII Olympiad in Sydney in 2000. This institution will have as its mandate, notably, to coordinate the various programmes necessary to realize the objectives that shall be defined jointly by all the parties concerned. Among these programmes, consideration should be given in particular to expanding out-of-competition testing, coordinating research, promoting preventive and educational actions and harmonizing scientific and technical standards and procedures for analyses and equipment. A working group representing the Olympic Movement, including the athletes, as well as the governments and inter-governmental organizations concerned, will meet, on the initiative of the IOC, within three months, to define the structure, mission and financing of the Agency. The Olympic Movement commits to allocate a capital of US $25 million to the Agency. 5. Responsibilities of the IOC, the IFs, the NOCs and the CAS The IOC, the IFs and the NOCs will maintain their respective competence and responsibility to apply doping rules in accordance with their own procedures, and in cooperation with the International Anti-Doping Agency. Consequently, decisions handed down in the first instance will be under the exclusive responsibility of the IFs, the NOCs or, during the Olympic Games, the IOC. With regard to last instance appeals, the IOC, the IFs and the NOCs recognize the authority of the Court of Arbitration for Sport (CAS), after their own procedures have been exhausted. In order to protect athletes and their rights in the area of disciplinary procedure, the general principles of law, such as the right to a hearing, the right to legal assistance, and the right to present evidence and call witnesses, will be confirmed and incorporated into all applicable procedures. 6. Collaboration between the Olympic Movement and public authorities The collaboration in the fight against doping between sports organizations and public authorities shall be reinforced according to the responsibilities of each party. Together, they will also take action in the areas of education, scientific research, social and health measures to protect athletes, and coordination of legislation relative to doping.